THE RELATIONSHIP BETWEEN CHRISTIAN RELIGIOUS EDUCATION IN THE DIGITAL ERA AND THE FORMATION OF STUDENTS' SPIRITUALITY AT SMP NEGERI 1 MEDAN - Mei Pasaribu (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
This study aims to determine the significant relationship between Christian Religious Education and the Formation of Spirituality of VIII-grade Students at SMP Negeri 1 Pulau-Pulau Batu, South Nias, Academic Year 2022/2023. The population in this study were all VIII-grade students at SMP Negeri 1 Pulau-Pulau Batu, totaling 25 people, because the population was small, namely only 25 people, the entire population became the research sample, namely 25 people. This study used a quantitative method with SMART PLS software data processing. The method of collecting data as a result of the study was a questionnaire using a Likert scale with 4 answer options. The results of the study in measuring validity where the outer loading results of all indicators were > 0.7, this indicates that all indicators of variables X and Y can represent the latern variable (construct). Likewise, reliability where CA, RO, CR, > 0.7 and AVE > 0.5, shows that all indicators are reliable, so this result can be continued with hypothesis testing which shows that there is a relationship between Christian Religious Education and the Formation of Student Spirituality with T. statistic > T. table, namely 2.109 > 1.96 and p. value 0.035 > 0.05. The conclusion of this study shows that there is a relationship between Christian Religious Education and the Formation of Student Spirituality. (X) with Spiritual Formation (Y) but not significant.